Preparation process of low-internal-stress thick nano coating for erosion-resistant low-friction solid lubrication at high temperature

By depositing a multi-component coating of TiSiCN, CrSiCN, and TiAlSiCN on the workpiece surface and incorporating Si through PECVD plasma-enhanced deposition, the problem of low friction lubrication of the coating under high-temperature conditions in a strong granular erosion environment was solved, achieving hard, wear-resistant, and low-friction coating performance.

CN121006526APending Publication Date: 2025-11-25SHENZHEN HONGHEFU TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511143966.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-15
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing coating technologies struggle to achieve low-friction lubrication in high-temperature and intense particle erosion environments, leading to rapid workpiece failure.

Method used

A hybrid vapor deposition method combining PVD and PECVD is used to deposit a multi-element coating of TiSiCN, CrSiCN, and TiAlSiCN on the workpiece surface. Si is incorporated by plasma-enhanced deposition using PECVD to reduce internal stress and increase thickness, thus forming a hard and wear-resistant coating.

Benefits of technology

It achieves low friction coefficient and high erosion resistance at temperatures above 500℃, effectively resists erosion by high-speed jet particles, improves friction and wear performance, and realizes solid lubrication in high-temperature service environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation process of a low-internal-stress thick nano coating for erosion-resistant low-friction solid lubrication at high temperature. The preparation process comprises the following steps: pretreating a matrix; vacuumizing and heating; etching and cleaning Ar ions on the surface of the matrix; starting a rotating cathode or a planar cathode filled with metal target materials such as Ti and Cr or alloy target materials such as TiAl and TiZr, and introducing N2 gas to carry out magnetron reactive sputtering; the method comprises the following steps: starting a hot filament arc gas ion source, introducing Si-containing precursors such as TMS tetramethylsilane, HMDS hexamethyldisilazane and SiH4 silane beside the hot filament arc gas ion source to obtain active Si ion and Si-C ion functional ionic groups, and depositing TiSiCN, CrSiCN and TiAlSiCN multi-element coatings on the surface in the presence of metal ions, Si ions, Si-C ions and nitrogen. According to the method, the silicon-doped multi-element nitride coating is deposited innovatively through the PVD and PECVD mixed vapor deposition technology, the technical problem of collaborative optimization of high temperature, erosion and low friction is solved, and the performance blank of an existing coating under the extreme working condition is filled up.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of lubricating materials, in particular to a low-stress thick nanometer coating preparation process for erosion-resistant high-temperature low-friction solid lubrication. BACKGROUND

[0002] At present, coating technologies for high-temperature, erosion-resistant and low-friction requirements mainly include the following types: (1) traditional solid lubricating coatings (such as MoS2 and graphite). The friction coefficient can be low (0.02-0.1) at room temperature, and they are often used in vacuum or inert environments. However, they are prone to high-temperature oxidation failure, for example, MoS2 is oxidized to form MoO3 at more than 350 DEG C, losing lubricity; the erosion resistance is poor, and the soft layer is easily stripped by particle erosion; and they are not suitable for humid environments, and water vapor will accelerate the degradation of MoS2. (2) Oxide / carbon-based hard coatings (such as Cr2O3). This type of coating has good high-temperature stability (Cr2O3 temperature resistance > 1000 DEG C) and strong erosion resistance. However, the friction coefficient is high, the brittleness is large, and fatigue peeling is prone to occur. (3) Multi-layer / complex coating (such as TiAlN+WS2). The hard phase (erosion resistance) and the soft phase (lubrication) can be combined. The interface may diffuse at high temperatures, and the soft phase and the hard phase may react and fail; in addition, this type of process is complex and has high cost. (4) MAX phase coating (such as Ti3SiC2). It has metal / ceramic characteristics, and forms a lubricating oxide layer at high temperatures. However, the deposition rate is low in the traditional PVD process, which is difficult to industrialize, and the coating has high internal stress, poor erosion resistance, and is prone to cracking.

[0003] In summary, under harsh service conditions, whether the workpiece is a metal material or a material with an existing coating on the surface, it is difficult to achieve low-friction lubricity at more than 500 DEG C, in addition, the service environment is accompanied by strong particle erosion, which will cause the workpiece to fail rapidly and cause the entire system to shut down.

[0004] The application innovatively adopts a PVD and PECVD mixed gas deposition method to deposit TiSiCN, CrSiCN and TiAlSiCN multi-element coatings on the surface of a workpiece. Because the coating is not deposited by sputtering a Si-containing alloy target (in this method, Si cannot be completely ionized, that is, a large amount of elemental Si will exist, and the coating stress will also be very large), but Si is doped by PECVD plasma enhanced deposition, on the one hand, Si is completely ionized, and on the other hand, the internal stress of the deposited coating is very low, and the coating thickness can reach 20-100 mu m. A hard wear-resistant coating with such thickness can resist the erosion of high-speed jet particles. And the coating contains C, which has excellent low friction coefficient at more than 500 DEG C, so it can not only greatly improve the friction and wear performance, but also realize solid lubrication in high-temperature service environments. SUMMARY

[0005] The purpose of this invention is to provide a process for preparing a low-stress, thick nano-coating for erosion-resistant, high-temperature, low-friction solid lubrication. The specific steps of this preparation process are as follows:

[0006] Step 1: Pre-treat the workpiece by using an organic solvent to ultrasonically clean the workpiece, remove stains from the surface, and then blow dry.

[0007] Step 2: Vacuum heating;

[0008] Step 3: Ar ion etching and cleaning of the substrate surface;

[0009] Step 4: Start the rotating cathode or planar cathode containing the metal or alloy target and introduce N2 gas to perform magnetron reactive sputtering to deposit the transition layer;

[0010] Step 5: Start the rotating cathode or planar cathode containing the metal or alloy target and introduce N2 gas. At the same time, start the hot filament arc gas ion source and introduce the Si precursor next to it. Use the high-energy electron beam and Ar cations of the hot filament ion source to break down these precursors and obtain active Si ions and Si-C ion functional ion groups. In the presence of metal ions, Si ions, Si-C ions and nitrogen gas, deposit a silicon-doped multi-component nitride coating on the surface.

[0011] Preferably, in step two, the heating temperature is 400-550℃, the vacuum degree is 0.005-0.008Pa, and the time is 90-120min.

[0012] Preferably, in step three, the argon flow rate is 200-350 sccm, the vacuum degree is 0.06-0.09 Pa, the bias voltage is 200-400 V, the ion source current is 60-100 A, and the time is 60-80 min.

[0013] Preferably, the target material in step four includes metal targets such as Ti and Cr, or alloy targets such as TiAl and TiZr.

[0014] Preferably, in step four, the N2 gas flow rate is 500-800 sccm, the vacuum degree is 0.7-1.0 Pa, the bias voltage is 50-100 V, the target current is 20-30 A, and the time is 90-120 min.

[0015] Preferably, the Si-containing precursor in step five includes TMS tetramethylsilane, HMDS hexamethyldisilazane, and SiH4 silane.

[0016] Preferably, in step five, the N2 gas flow rate is 500-800 sccm, the Si precursor flow rate is 20-30 sccm, the vacuum degree is 0.7-1.0 Pa, the bias voltage is 30-80 V, the ion source current is 60-100 A, the target current is 20-30 A, and the time is 60-90 min.

[0017] Preferably, the ultrasonic cleaning in step one can also use deionized water.

[0018] Compared with existing technologies, the advantages of this invention are as follows: Due to the use of PECVD plasma-enhanced assisted deposition to incorporate Si, the deposited coating exhibits very low internal stress, and the coating thickness can reach 20-100 μm. Such a thick, hard, wear-resistant coating can resist the erosion of high-speed jet particles. The coating contains C, and it also possesses an excellent low coefficient of friction at temperatures above 500°C. Therefore, in addition to greatly improving friction and wear performance, it can also achieve solid lubrication functionality under high-temperature service environments, effectively solving the industry problem of high-temperature lubrication. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0020] Specific Implementation Method 1: This implementation method describes a method for preparing a low-stress, thick nano-coating for erosion-resistant, high-temperature, low-friction solid lubrication, which is carried out according to the following steps:

[0021] Step 1: Pre-treat the workpiece by using organic solvents or deionized water to ultrasonically clean the workpiece, remove stains from the surface, and then blow dry.

[0022] Step 2: Vacuum heating. The heating temperature is 400-550℃, the vacuum degree is 0.005-0.008Pa, and the time is 90-120 minutes.

[0023] Step 3: Ar ion etching and cleaning of the substrate surface. Argon flow rate 200-350 sccm, vacuum degree 0.06-0.09 Pa, bias voltage 200-400 V, ion source current 60-100 A, time 60-80 min.

[0024] Step 4: Start the rotating cathode equipped with metal targets such as Ti and Cr and introduce N2 gas to perform magnetron reactive sputtering to deposit the transition layer. The N2 gas flow rate is 500-800 sccm, the vacuum degree is 0.7-1.0 Pa, the bias voltage is 50-100 V, the target current is 20-30 A, and the time is 90-120 min.

[0025] Step 5: Start the rotating cathode containing metal targets such as Ti and Cr and introduce N2 gas. Simultaneously, start the hot filament arc gas ion source and introduce TMS tetramethylsilane next to it. Utilize the high-energy electron beam and Ar cations from the hot filament ion source to cleave the Si-containing precursor, obtaining active Si ions and Si-C functional ion groups. In the presence of metal ions, Si ions, Si-C ions, and nitrogen gas, deposit a silicon-doped multi-component nitride coating on the surface. N2 gas flow rate: 500-800 sccm; Si-containing precursor flow rate: 20-30 sccm; vacuum: 0.7-1.0 Pa; bias voltage: 30-80 V; ion source current: 60-100 A; target current: 20-30 A; time: 60-90 min.

[0026] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that a planar cathode is used in steps four and five. Everything else is the same as in Specific Implementation Method One.

[0027] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One in that steps four and five use alloy targets such as TiAl and TiZr. Everything else is the same as in Specific Implementation Method One.

[0028] Specific Implementation Method Four: This implementation method differs from Specific Implementation Method One in that step four uses metal targets such as Ti and Cr, while step five uses alloy targets such as TiAl and TiZr. Everything else is the same as in Specific Implementation Method One.

[0029] Specific Implementation Method Five: This implementation method differs from Specific Implementation Method One in that the Si-containing precursor used in step five is one or more of TMS tetramethylsilane, HMDS hexamethyldisilazane, and SiH4 silane, mixed in any proportion. Everything else is the same as in Specific Implementation Method One.

[0030] The following embodiments are a further detailed description of the present invention. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.

[0031] Example 1

[0032] The specific process steps for depositing a TiSiCN multi-element coating are as follows:

[0033] Step 1: Pre-treat the workpiece by using organic solvents or deionized water to ultrasonically clean the workpiece, remove stains from the surface, and then blow dry.

[0034] Step 2: Vacuum heating. The heating temperature is 400-550℃, the vacuum degree is 0.005-0.008Pa, and the time is 90-120 minutes.

[0035] Step 3: Ar ion etching and cleaning of the substrate surface. Argon flow rate 200-350 sccm, vacuum degree 0.06-0.09 Pa, bias voltage 200-400 V, ion source current 60-100 A, time 60-80 min.

[0036] Step 4: Start the planar cathode equipped with the TiAl alloy target and introduce N2 gas for magnetron reactive sputtering to deposit the TiAlN transition layer. The N2 gas flow rate is 500-800 sccm, the vacuum degree is 0.7-1.0 Pa, the bias voltage is 50-100 V, the target current is 20-30 A, and the time is 90-120 min.

[0037] Step 5: Turn off the TiAl alloy target, start the planar cathode containing the Ti metal target and introduce N2 gas, simultaneously start the hot filament arc gas ion source, and introduce TMS tetramethylsilane next to it. Utilize the high-energy electron beam and Ar cations from the hot filament ion source to decompose the Si-containing precursor, obtaining active Si ions and Si-C functional ion groups. In the presence of metal ions, Si ions, Si-C ions, and nitrogen gas, deposit a TiSiCN coating on the surface. N2 gas flow rate: 500-800 sccm; TMS tetramethylsilane flow rate: 20-30 sccm; vacuum: 0.7-1.0 Pa; bias voltage: 30-80 V; ion source current: 60-100 A; target current: 20-30 A; time: 60-90 min.

[0038] Tests showed that the coating has a scratch adhesion strength of 75-85N, a nano-indentation hardness of 38-42GPa, and a coefficient of friction of 0.38-0.45 at 500℃.

[0039] Example 2

[0040] The specific process steps for depositing a CrSiCN multi-element coating are as follows:

[0041] Step 1: Pre-treat the workpiece by using organic solvents or deionized water to ultrasonically clean the workpiece, remove stains from the surface, and then blow dry.

[0042] Step 2: Vacuum heating. The heating temperature is 400-550℃, the vacuum degree is 0.005-0.008Pa, and the time is 90-120 minutes.

[0043] Step 3: Ar ion etching and cleaning of the substrate surface. Argon flow rate 200-350 sccm, vacuum degree 0.06-0.09 Pa, bias voltage 200-400 V, ion source current 60-100 A, time 60-80 min.

[0044] Step 4: Start the planar cathode containing the Cr metal target and introduce N2 gas for magnetron reactive sputtering to deposit the CrN transition layer. The N2 gas flow rate is 500-800 sccm, the vacuum degree is 0.7-1.0 Pa, the bias voltage is 50-100 V, the target current is 20-30 A, and the time is 90-120 min.

[0045] Step 5: While maintaining the Cr metal target on and N2 gas flow, simultaneously activate the hot filament arc gas ion source and introduce TMS tetramethylsilane next to it. Utilize the high-energy electron beam and Ar cations from the hot filament ion source to cleave the Si-containing precursor, obtaining active Si ions and Si-C functional ion groups. In the presence of metal ions, Si ions, Si-C ions, and nitrogen gas, deposit a CrSiCN coating on the surface. N2 gas flow rate: 500-800 sccm; TMS tetramethylsilane flow rate: 20-30 sccm; vacuum: 0.7-1.0 Pa; bias voltage: 30-80 V; ion source current: 60-100 A; target current: 20-30 A; time: 60-90 min.

[0046] Tests showed that the coating has a scratch adhesion strength of 85-95N, a nano-indentation hardness of 30-35GPa, and a coefficient of friction of 0.35-0.40 at 500℃.

[0047] Example 3

[0048] The specific process steps for depositing a TiAlSiCN multi-element coating are as follows:

[0049] Step 1: Pre-treat the workpiece by using organic solvents or deionized water to ultrasonically clean the workpiece, remove stains from the surface, and then blow dry.

[0050] Step 2: Vacuum heating. The heating temperature is 400-550℃, the vacuum degree is 0.005-0.008Pa, and the time is 90-120 minutes.

[0051] Step 3: Ar ion etching and cleaning of the substrate surface. Argon flow rate 200-350 sccm, vacuum degree 0.06-0.09 Pa, bias voltage 200-400 V, ion source current 60-100 A, time 60-80 min.

[0052] Step 4: Start the planar cathode equipped with the TiAl alloy target and introduce N2 gas for magnetron reactive sputtering to deposit the TiAlN transition layer. The N2 gas flow rate is 500-800 sccm, the vacuum degree is 0.7-1.0 Pa, the bias voltage is 50-100 V, the target current is 20-30 A, and the time is 90-120 min.

[0053] Step 5: While maintaining the TiAl alloy target on and N2 gas flow, simultaneously activate the hot filament arc gas ion source and introduce TMS tetramethylsilane next to it. Utilize the high-energy electron beam and Ar cations from the hot filament ion source to decompose the Si-containing precursor, obtaining active Si ions and Si-C functional ion groups. In the presence of metal ions, Si ions, Si-C ions, and nitrogen gas, deposit a TiAlSiCN coating on the surface. N2 gas flow rate: 500-800 sccm; TMS tetramethylsilane flow rate: 20-30 sccm; vacuum: 0.7-1.0 Pa; bias voltage: 30-80 V; ion source current: 60-100 A; target current: 20-30 A; time: 60-90 min.

[0054] Tests showed that the coating has a scratch adhesion strength of 75-85N, a nano-indentation hardness of 35-40GPa, and a coefficient of friction of 0.38-0.45 at 500℃.

[0055] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A process for preparing a low-internal-stress thick nano-coating for erosion-resistant, high-temperature, low-friction solid lubrication, characterized in that: The specific steps of the preparation process are as follows: Step 1: Pre-treat the workpiece by using an organic solvent to ultrasonically clean the workpiece, remove stains from the surface, and then blow dry. Step 2: Vacuum heating; Step 3: Ar ion etching and cleaning of the substrate surface; Step 4: Start the rotating cathode or planar cathode containing the metal or alloy target and introduce N2 gas to perform magnetron reactive sputtering to deposit the transition layer; Step 5: Start the rotating cathode or planar cathode containing the metal or alloy target and introduce N2 gas. At the same time, start the hot filament arc gas ion source and introduce the Si precursor next to it. Use the high-energy electron beam and Ar cations of the hot filament ion source to break down these precursors and obtain active Si ions and Si-C ion functional ion groups. In the presence of metal ions, Si ions, Si-C ions and nitrogen gas, deposit a silicon-doped multi-component nitride coating on the surface.

2. The preparation process of a low-stress thick nano-coating for erosion-resistant, high-temperature, low-friction solid lubrication according to claim 1, characterized in that: In step two, the heating temperature is 400-550℃, the vacuum degree is 0.005-0.008Pa, and the time is 90-120min.

3. The preparation process of a low-stress thick nano-coating for erosion-resistant, high-temperature, low-friction solid lubrication according to claim 1, characterized in that: In step three, the argon flow rate is 200-350 sccm, the vacuum degree is 0.06-0.09 Pa, the bias voltage is 200-400 V, the ion source current is 60-100 A, and the time is 60-80 min.

4. The preparation process of a low-stress thick nano-coating for erosion-resistant, high-temperature, low-friction solid lubrication according to claim 1, characterized in that: The target material in step four includes Ti and Cr metal targets or TiAl and TiZr alloy targets.

5. The preparation process of a low-stress thick nano-coating for erosion-resistant, high-temperature, low-friction solid lubrication according to claim 1, characterized in that: In step four, the N2 gas flow rate is 500-800 sccm, the vacuum degree is 0.7-1.0 Pa, the bias voltage is 50-100 V, the target current is 20-30 A, and the time is 90-120 min.

6. The preparation process of a low-stress thick nano-coating for erosion-resistant, high-temperature, low-friction solid lubrication according to claim 1, characterized in that: The Si-containing precursors in step five include TMS tetramethylsilane, HMDS hexamethyldisilazane, and SiH4 silane.

7. The preparation process of a low-stress thick nano-coating for erosion-resistant, high-temperature, low-friction solid lubrication according to claim 1, characterized in that: In step five, the N2 gas flow rate is 500-800 sccm, the Si precursor flow rate is 20-30 sccm, the vacuum degree is 0.7-1.0 Pa, the bias voltage is 30-80 V, the ion source current is 60-100 A, the target current is 20-30 A, and the time is 60-90 min.

8. The preparation process of a low-stress thick nano-coating for erosion-resistant, high-temperature, low-friction solid lubrication according to claim 1, characterized in that: The ultrasonic cleaning in step one can also be done using deionized water.

Citation Information

Patent Citations

  • Super-thick super-hard coating and preparation method thereof

    CN102756514A

  • Wear-resistant TiSiCN film preparation method

    CN107641792A

  • Preparation method of TiSiCN film with adjustable components

    CN107641793A

  • Preparation method for super-hard and tough TiSiCN hard coating

    CN110129742A

  • Preparation device and preparation method of nano-composite MeSiCN coating

    CN114672774A